Evaluation Study of Different Techniques in Diagnosis of Acute Leukemia in Adults and Children Patients - Rash Hamid Ayub1 , Ayad Hameed Ibraheem2, Najwan Salih Nima3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cytomorphology and cytochemistry are combined with immunophenotype by flow cytometry (FCM) todiagnosis and management the acute leukemia. The present study was designed to compare between thecytomorphology, cytochemistry and immunophenotype by flow cytometry at diagnosis and classification ofacute leukemia to suggest a number of antibodies that can be adopted in the diagnosis by flow cytometry.The study included (160) cases were newly diagnosed (100 adults, 60 children). Morphological analysiswas depended on peripheral blood smears examination by Leishman stain, cytochemical analysis with PASand SBB stains and immunophenotype analysis used multiparameter. the results of this study shown that60% of adult cases were AML, and 40% ALL. The mean age of adults was 48.45 years for AML cases andwas 32.59 years for ALL adult cases. In children AML the mean age was 5.23 years and was 6.44 years inchildren ALL cases. Our Conclusion Also that the B.ALL was more commonly than T.ALL in both adultsand children cases. Immunophenotypic detection by flow cytometry recorded (100%) successfully diagnosisin ALL cases, but it was successfully in (75%) of detected the subtypes of AML cases.